(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The purpose of study is to analyze the impact of fair accounting on the accuracy of financial asset valuation, the role of accounting disclosure in enhancing the reliability of financial statements, and analyzing the relationship between the level of accounting disclosure and the accuracy of financial valuation. Additionally, it concentrates on the challenges that fronting financial institutions in adopting this method, especially related to the provision of accurate data that supports fair valuation. The study’s importance lies in analyzing the relationship between fair accounting and the accuracy of financial asset valuation, and the role of accounting disclosure in achieving financial information transparency and enhancing its reliability. The problem’s study is to inspect the relationship between the use of fair accounting methods and the accuracy of financial asset valuation through effective accounting disclosure. The study concludes that the applying fair accounting contributes to improving the reliability of financial statements, minimizing accounting biases, rising the confidence of investors and stakeholders, and improving the efficiency of financial markets. However, the success of this application depends on several factors, including the level of accounting disclosure, the availability of market data, and companies’ compliance with international accounting standards. The study also discovers that companies invest in enhancing accounting disclosure and improving the accuracy of financial valuations greater competitiveness in financial markets. The recommendations study is improving the company’s financial disclosure systems by adopting the recent global practices, matching the International Financial Reporting Standards (IFRS). ensuring effective application of fair accounting, moreover recommended to provide ongoing training programs for accountants and administrators on the latest developments in this field.